2022
DOI: 10.1016/j.jagp.2022.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Functional Impact of COVID-19 in Long-Term Care Facilities: The COVID-A Study

Abstract: Objective To analyze the psychological and functional sequelae of the COVID-19 pandemic among older adults living in long term care facilities (LTCFs). Design : Cohort longitudinal study Setting ant participants : 215 residents ≥ 65 years without moderate-to-severe cognitive impairmen, living in five LTCFs in Albacete (Spain). Measurements : Baseline on-site data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…The current issue of the American Journal of Geriatric Psychiatry features a noteworthy study by Cortes-Zamora and colleagues 14 who present longitudinal data on 215 cognitively intact long-term care facility (LTCF) residents in Spain. Analyzing data collected between March and September 2020, they compared outcomes among those who contacted COVID-19 vs. those who did not.…”
Section: Understanding Trends and Factors Impacting Mental Health Imp...mentioning
confidence: 99%
“…The current issue of the American Journal of Geriatric Psychiatry features a noteworthy study by Cortes-Zamora and colleagues 14 who present longitudinal data on 215 cognitively intact long-term care facility (LTCF) residents in Spain. Analyzing data collected between March and September 2020, they compared outcomes among those who contacted COVID-19 vs. those who did not.…”
Section: Understanding Trends and Factors Impacting Mental Health Imp...mentioning
confidence: 99%
“… 22 , 23 , 28 Functional decline has occurred in LTC residents without dementia regardless of COVID‐19 infection status, suggesting that factors beyond those due to COVID‐19 infection are partly responsible for the negative impact of the pandemic in residential care settings. 29 Our findings that nearly half of respondents did not perceive any worsening of overall quality of dementia care and the minimal perceived increase in physical restraint use during the pandemic are encouraging. The latter may be a result of longstanding quality improvement efforts aimed at limiting the use of restraints in LTC in Canada.…”
Section: Discussionmentioning
confidence: 60%
“…Social isolation resulting from infection control measures and visitor restrictions may also be responsible for the negative effects of COVID‐19 on persons with dementia in LTC, given the known benefits of social contact in dementia 22,23,28 . Functional decline has occurred in LTC residents without dementia regardless of COVID‐19 infection status, suggesting that factors beyond those due to COVID‐19 infection are partly responsible for the negative impact of the pandemic in residential care settings 29 . Our findings that nearly half of respondents did not perceive any worsening of overall quality of dementia care and the minimal perceived increase in physical restraint use during the pandemic are encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Several countries imposed restrictions on external visits and internal activities to contain the spread of the disease [ 2 4 ], which was indeed more dangerous within institutions where highly susceptible people were clustered in one place [ 1 ] and where higher mortality rates due to the disease were reported [ 5 ]. The lack of activities and family visits affected the older adults living in these institutions worldwide, who were further isolated due to the demands of the restrictive measures, presenting increased depressive symptoms and anxiety, reduced mental acuteness, physical capacity, well-being, and quality of life due to the lack of social connectedness and other factors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have analyzed the impacts of the volunteer activities interrupted due to the COVID-19 pandemic on healthcare institutions, their patients, and volunteers, and reported increased staff workload [ 2 ] and negative impacts on the health and well-being of older adult volunteers [ 15 ]. The literature in the context of long-term care institutions (disregarding volunteer activity specifically) has reported negative impacts of the restrictions on residents, which include reduced mental well-being [ 16 ], cognitive performance, quality of life [ 17 ],functional decline [ 7 ], as well as increased feelings of anxiety, of loneliness, and depressive symptoms [ 18 ]. Other studies have also reported negative effects on family members and visitors of the residents, reporting low emotional and psychological well-being [ 19 ], and feelings of anxiety, frustration, and guilt [ 18 ].…”
Section: Introductionmentioning
confidence: 99%